Perancangan Rotor Turbin Angin Savonius Tipe-L Untuk Pembangkit Listrik Pada Rumah Tinggal - Woe Junior; Stenly Tangkuman; Tritiya Arungpadang (JURNAL POROS TEKNIK MESIN UNSRAT, 2022)
Rotor is one of the main component in wind power plant. The rotor plays a role in converting wind energy into rotary energy / mechanical energy. To connect the rotor to the gear requires a shaft. This research aims to design a rotor Savonius Wind Turbine with an L blade type for a Wind Power Plant. This research has two purposes, first to design the Rotor Savonius Wind Turbine and then simulate the rotor in the Ansys Workbench 18.1 to sees the output power. Second is making a Rotor to complete a miniature Wind Power Plant with a ratio of 1:5.             The result of the Rotor design is that the diameter is 1.25 m and the height is 2.5 m. Can operate at 6.25 m/s with the output power is 120 Watt. The rotor miniature can function properly and has been installed on a miniature Wind Power Plant. Keywords: Rotor, Wind Power Plant